Mid-term results of a modified self-growing rod technique for the treatment of early-onset scoliosis. (2nd November 2020) - Mehdian, Hossein; Haddad, Sleiman; Pasku, Dritan; Nasto, Luigi Aurelio
Abstract : Aims: To report the mid-term results of a modified self-growing rod (SGR) technique for the treatment of idiopathic and neuromuscular early-onset scoliosis (EOS). Methods: We carried out a retrospective analysis of 16 consecutive patients with EOS treated with an SGR construct at a single hospital between September 2008 and December 2014. General demographics and deformity variables (i.e. major Cobb angle, T1 to T12 length, T1 to S1 length, pelvic obliquity, shoulder obliquity, and C7 plumb line) were recorded preoperatively, and postoperatively at yearly follow-up. Complications and revision procedures were also recorded. Only patients with a minimum follow-up of five years after surgery were included. Results: A total of 16 patients were included. Six patients had an idiopathic EOS while ten patients had a neuromuscular or syndromic EOS (seven spinal muscular atrophy (SMA) and three with cerebral palsy or a syndrome). Their mean ages at surgery were 7.1 years (SD 2.2) and 13.3 years (SD 2.6) respectively at final follow-up. The mean preoperative Cobb angle of the major curve was 66.1° (SD 8.5°) and had improved to 25.5° (SD 9.9°) at final follow-up. The T1 to S1 length increased from 289.7 mm (SD 24.9) before surgery to 330.6 mm (SD 30.4) immediately after surgery. The mean T1 to S1 and T1 to T12 growth after surgery were 64.1 mm (SD 19.9) and 47.4 mm (SD 18.8), respectively, thus accounting for a mean T1 to S1 and T1 to T12 spinal growth after surgery of 10.5 mm/year (SD 3.7) and 7.8 mm/year (SD 3.3), respectively. A total of six patients (five idiopathic EOS, one cerebral palsy EOS) had broken rods during their growth spurt but were uneventfully revised with a fusion procedure. No other complications were noted. Conclusion: Our data show that SGR is a safe and effective technique for the treatment of EOS in nonambulatory hypotonic patients with a neuromuscular condition. Significant spinal growth can be expected after surgery and is comparable to other published techniques for EOS. While satisfactory correction of the deformity can be achieved and maintained with this technique, a high rate of rod breakage was seen in patients with an idiopathic or cerebral palsy EOS. Cite this article: Bone Joint J 2020;102-B(11):1560–1566.